Current health service demands of new residents in shanghai - SHI Jiahua; HUANG Mingmin; SUN Yongmei; WANG Jiacheng; GUO Jie; QI Yongming; TANG Qiong (Shanghai yufang yixue, 2022)
ObjectiveTo understand the current situation and influencing factors of health service demands of new residents in Shanghai.MethodsFrom July to August 2020， a questionnaire survey was conducted in 1 358 new residents from 36 survey points in 7 districts of the city. The questionnaire included the basic medical insurance coverage in the inflow area， the current situation of medical demand and related influencing factors， and the demands for other health services.Results47.1%（562/1 194）of new residents did not choose to seek timely medical treatment when they were not feeling well. The main reason was that the working hours occupied the medical treatment time. Logistic regression analysis showed that the main factors affecting the medical needs in new residents were the average daily working hours， living area and type of residence， health status， physical examination and physical exercise， and the type of basic medical insurance. The demands of new residents for "health consultation of common diseases and frequently occurring diseases"， "health behavior intervention （such as smoking cessation and alcohol restriction）"， "medical guidance and publicity"， "accidental injury prevention （traffic， work， falling， etc.）" and "maintenance of legitimate rights and interests of health" were 57.1%（682/1 194）、41.3%（493/1 194）、34.9%（417/1 194）、32.2%（385/1 194） and 31.9%（381/1 194）， respectively.ConclusionNew residents demands for medical services cannot be met. We should actively improve the working and living conditions of new residents， improve the construction of new residents' health service system， and improve the utilization level of health services.